Knowledge management processes and sustainable competitive advantage: An empirical examination in private universities - Mahdi O.R.; Nassar I.A.; Almsafir M.K. (Elsevier Inc., 2023)
In modern times, it has come to the realization of organizations that acquiring knowledge and using it in an effective manner is the only way to have a sustainable competitive advantage (SCA) in the marketplace. This means that the resources of an organization must include knowledge, which should always be cared for and developed upon. When it comes to private colleges and universities, these are really just investments for the future businesspeople of the world. Through knowledge management processes (KMP), the knowledge they end up processing from these educational institutions will help them decide the direction in which they go in the future and how competitive they will be in the business world. But when it comes to knowledge-based view (KBV) and resource-based view (RBV), there is no clear explanation between them and how much the competitive advantage that KMP provides can be sustained. In this study, we will look at how and why SCA can be created by KMP from the educational environment's KBV and RBV. In order to achieve the objective, a hypothesis was created along with a quantitative survey method of design. The initiation of the structural equation modelling (SEM) method helped determine the relationship between the study variables through deductive approach. The respondents of this study are comprised of 525 academic leaders with varying positions from 44 private Iraqi universities. The results show a significant relationship between KMP and SCA. To attain a better SCA, private universities must generate knowledge, store knowledge, share knowledge and apply knowledge that is backed by identify of knowledge and formulating of its goals throughout every aspect of the organization. The research adds to the active group of knowledge that is currently available in the area of strategic knowledge management. 2018 Elsevier Inc.